2015
DOI: 10.1364/boe.6.004841
|View full text |Cite
|
Sign up to set email alerts
|

Impact of scatter on double-pass image quality and contrast sensitivity measured with a single instrument

Abstract: Abstract:We compared objective Double-Pass (DP) image quality data with subjective visual parameters measured within the same modified instrument for different amounts of scatter. The original DP imaging channel of a clinical instrument was maintained intact and two additional channels were included, one for visual testing and another for tear film (TF) imaging by using a retro-illumination technique. Contrast sensitivity (CS) was compared with measurements of the Objective Scattering Index (OSI) obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…Figure 6 shows the results of CSF for all subjects measured with and without scatter filters. It can be observed that the CS decreased with increasing scatter for each spatial frequency, which was consistent with the previous results reported by Bueno et al [10]. For a better understanding of the effect of scatter on visual performance, parameter Impact factor Scatter was computed for each scatter filter and spatial frequency.…”
Section: Contrast Sensitivity At Different Scatter Levels After Hoas supporting
confidence: 89%
See 4 more Smart Citations
“…Figure 6 shows the results of CSF for all subjects measured with and without scatter filters. It can be observed that the CS decreased with increasing scatter for each spatial frequency, which was consistent with the previous results reported by Bueno et al [10]. For a better understanding of the effect of scatter on visual performance, parameter Impact factor Scatter was computed for each scatter filter and spatial frequency.…”
Section: Contrast Sensitivity At Different Scatter Levels After Hoas supporting
confidence: 89%
“…Results showed that CS decreased with increasing scatter and AO correction of HOAs improved CS in all spatial frequencies for each subject, suggesting that both HOAs and intraocular scatter played an essential role in the CSF. To date, there have been several studies [8,10] assessing the respective effect of HOAs and intraocular scatter on CSF, and similar results were reported. Kang et al [8] measured the CS with and without HOAs correction, and their results showed that AO correction of HOAs improved CS for all spatial frequencies in all eyes.…”
Section: Contrast Sensitivity At Different Scatter Levels Before Hoassupporting
confidence: 52%
See 3 more Smart Citations